Graham Greene’s The Heart of the Matter: A Literary Challenge to the Catholic Faith - Mourad MAIMOUNE; Sara TABZA (International Journal of Scientific Research and Innovative Studies, 2026)
This paper examines Graham Greene’s The Heart of the Matter as a critical engagement with Roman Catholic doctrine through the lens of the author’s “uneasy Catholicism”. It argues that Greene, often labelled a “Catholic novelist”, in fact adopts a persistently sceptical stance toward Catholic teachings, shaped by his self-described position as an “agnostic Catholic”. The study first outlines Greene’s complex relationship with faith, highlighting his intellectual conversion to Catholicism and his enduring doubts regarding the existence and nature of God. It then provides a concise overview of key Catholic doctrines, particularly the seven sacraments and the concepts of salvation and damnation, which structure the moral universe that the novel interrogates. The analysis demonstrates how The Heart of the Matter functions as a critique of institutional Catholicism through the tragic trajectory of Henry Scobie. While initially portrayed as morally upright, Scobie’s excessive sense of responsibility and compassion ultimately lead him into adultery, guilt, and suicide. The novel is read as exposing tensions within Catholic doctrine: marriage appears as a source of moral entrapment rather than sanctification, confession fails to provide genuine spiritual relief, clerical authority proves inadequate in addressing psychological and moral doubt, and the doctrine of damnation is revealed as rigid and ethically problematic when confronted with human complexity. Through Scobie’s inner conflict and eventual despair, Greene highlights the gap between doctrinal absolutism and lived moral experience. The paper concludes that the novel does not simply reject Catholicism but rather critiques its inflexibility, suggesting the need for a more adaptive and humane understanding of religious practice. In doing so, Greene exposes tragic contradictions within Christian morality itself and raises a broader question about whether religion should dictate human experience or evolve in response to it. Keywords: The Heart of the Matter; Graham Green; Roman Catholicism; Faith and Doubt; Institutional Critique; Christian Morality. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/668